1832 Del. Laws 208, A Supplement to an Act to Prevent the Use of Firearms by Free Negroes and Free Mulattoes, and for Other Purposes, ch. 176, § 1 - (:unkn) unknown (General Publisher, 1832)
Prohibited “free negroes and free mulattoes” from having, owning, keeping, or possessing any gun, pistol, sword, or warlike instrument without permission of five or more citizens of the neighborhood.
--
Keywords: ENSLAVED PERSONS & OTHER MINORITIES